An examination of selling forbidden meat to unbelievers - Ã˜Â§Ã˜ÂÃ™Â…Ã˜Â¯Ã™Â¾Ã™ÂˆÃ˜Â±, Ã˜Â§ÃšÂ©Ã˜Â¨Ã˜Â± (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
The question has long been asked whether the meat of animals not purified in accordance with Islamic law and thus considered âdeadâ can be sold to non-Muslims who do not adhere to Islamic legal purification. Can the profits of such a trade be earned and enjoyed, or will it be unlawful and prohibited? In fact, selling âthe deadâ in terms of their non-food advantages, whether to Muslims or unbelievers, has been considered as permissible by a number of jurists. Nevertheless, as regards their trade for edible consumption, most jurists favor the jurisprudential theory advancing the prohibition of selling âthe deadâ even to non-Muslims. The present article, however, is in favor of selling forbidden meat to unbelievers. Hence, this study analyzes and critiques the reasons proposed by those who consider this trade as prohibited. In addition, a number of reasons supporting the notion of permissibility will be provided.